Development of a Holistic Teacher Performance Evaluation Model at Catholic High Schools in Manado - Antonius Heatubun; Joulanda A M Rawis; Tinneke E. M. Sumual; Theodorus Pangalila (JR Education, 2026)
This study aims to develop a holistic and contextual teacher performance evaluation model for Catholic senior high schools in Manado. The study is motivated by the limitations of existing evaluation systems, which tend to focus primarily on pedagogical and professional aspects and have not fully integrated personality, social, and spiritual dimensions. The research approach combines theoretical analysis with empirical findings obtained through needs assessment and field study, resulting in a model construction that is relevant to the context of Catholic education. The findings indicate that the current evaluation system remains administrative and partial in nature and is not yet supported by comprehensive evaluation instruments. Therefore, a holistic teacher performance evaluation model was developed, encompassing five main dimensions: pedagogical, professional, personality, social, and spiritual. This model is designed as an integrated evaluation system oriented toward the comprehensive development of teachers and aligned with the values of Catholic education. The implications of this study highlight the importance of transforming evaluation systems toward a more comprehensive approach, utilizing multidimensional instruments, and strengthening both teacher professionalism and spirituality. The developed model has the potential to be utilized as a conceptual framework for schools, teachers, educational foundations, and policymakers in improving educational quality. However, this model remains conceptual and requires further empirical validation through subsequent studies to examine its feasibility, practicality, and effectiveness in broader implementation.